Strategies for Implementing Information Policy by the National Libraries in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This paper discussed the strategies for implementing information policy by the National Libraries in Nigeria being desirable in the face of the emergence of an information society. A National Library is a library established by the government as a country’s pre-eminent repository of information. Unlike public libraries, these rarely allows citizens to borrow books. Often they include numerous rare, valuable, or significant works. A National Library is that Library which has the duty of collecting and preserving the Literature of the nation within and outside the country. Information policies are a social political regulation, economic and technological decision related to the role of information in society (2003). In a nutshell information policy is a set of regulations and policies guiding information.